Effects of non-invasive ventilatory support in tolerance to the effort of patients with hemodialysis - Nathalie Cortez Bezerra de Medeiros; Joelson dos Santos Silva; Nayara Priscila Dantas de Oliveira; Ananília Regina Silva Cavalcante; Carolina Taveira Gonçalves; Karla Luciana Magnani
Abstract Introduction The kidney system is responsible for the maintenance of homeostasis and in patients with Chronic Kidney Disease the kidney functions changes, contributing for the development of various complications that will have adverse effects in tolerance to the physical exercise and in Quality of Life of this patients. Objective To evaluate the Effects of non-invasive ventilatory support in tolerance to the patients' physical exercise in dialysis. Methods The patients performed two 6-minute walk tests, following an adapted protocol for treadmill, one of them without the use of non-invasive ventilatory support and the other with non-invasive ventilatory support during the walk. Besides, the patients answered a questionnaire of quality of life and the KDQOL-SFTM specific for the population under study. Results It was noticed that there was not statistical difference in the distance recorded during the 6-minute walk tests. Regarding the quality of life, the greater impact of the disease was in relation to "Professional Activity". Conclusion In conclusion, a non-invasive ventilatory support did not cause significant effects in tolerance to the exercise of this population. However, we should take into consideration the limitations suffered during the research development.